INFLUENCE MIX PROMOTION AND BRAND COMPANY TO SATISFACTION BUYER ON PT. ALPHA SCORPIIMEDAN - Polma (Jurnal Enterprise dan Tata Kelola Perusahaan : Manajemen dan Akuntansi, 2025)
Objective from study This is aim For add outlook about Promotion And Brand in increase Satisfaction Buyer on PT. Alpha Scropii Medan. Study This use data primary population in study This as much as 300 person buyer with sample 75 respondents with formula Slovin. Method analysis data Which used is method analysis quantitative that is covering test validity, test reliability, test assumptions classic, analysis regression linear simple, testing hypothesis through t-test And test coefficient determination (R 2 ). Variables Mix Promotion E_Prmsi with t count as big as (-)1,824 with significance 0.072 > 0.05 And t table 1.99346. So t count < t table, that variables Mix Promotion Not yet own contribution to  Satisfaction Buyer. Mark t negative show variables Mix Promotion have connection Which No one way with Satisfaction Buyer. Results test partial t show that Brand Company own significance 0.00 < 0.05 so that concluded brand company  have contribution in a way partial influential to Satisfaction Buyer, hypothesis study H1 accepted. Results test determination on column R Square as big as 0.495, Because We use 2 direction regression multiple. With thus Influence Mix Promotion And Brand Company to Satisfaction Buyer that is as big as 49.5 % whereas the rest 50.5 % influenced by variables other Which No including in variables study. Recommended to head branch PT. ALPHA SCORPII Medan do Mix Promotion in a way economical, efficiency And effective as well as delivery advertisement Which delivered use media social like Facebook, Instagram, Twitter, or media print  Newspaper.